Solubilization and deaggregation of cobalt bis(dicarbollide) derivatives in water by biocompatible excipients - Rak, Jakub; Kaplánek, Robert; Král, Vladimír (Bioorganic & medicinal chemistry letters, 2010)
In the field of medicinal chemistry, cobalt bis(dicarbollide) derivatives are promising therapeutic agents. The potential pharmaceutical utilization of metallacarboranes is complicated due to spontaneous self-assembling in water. This problem can be solved by using suitable deaggregating agent. We present here the comprehensive screen of substituted cobalt bis(dicarbollide) derivatives with cyclodextrin derivatives, classical surfactants and amphiphilic copolymers to find general biocompatible excipients. Preliminary results are obtained by using UV/Vis spectroscopy as the technique with the best ratio of applicable information to time and source dependence.
Keywords: pomocné látky; kobalt; rozpustnost; Water; Humans; Excipients; lidé; Cobalt; voda; Solubility